1998
DOI: 10.1016/s0014-5793(98)01305-2
|View full text |Cite
|
Sign up to set email alerts
|

A cooperative model for protonmotive heme‐copper oxidases. The role of heme a in the proton pump of cytochrome c oxidase

Abstract: Oxido-reductions of metal centers in cytochrome c oxidase are linked to pK shifts of acidic groups in the enzyme (redox Bohr effects). The linkage at heme a results in proton uptake from the inner space upon reduction and proton release in the external space upon oxidation of the metal. The relationship of this process to the features of the proton pump in cytochrome c oxidase and its atomic structure revealed by X-ray crystallography to 2.8^2.3 A î resolution is examined. A mechanism for the proton pump of cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
24
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 54 publications
(166 reference statements)
2
24
1
Order By: Relevance
“…7 and 33), even though these two events have the same proton-limited kinetics. This finding is consistent with the conclusion by Brändén et al (34) that protonation of the ''pump site'' controls this electron transfer, which is of considerable mechanistic interest because much previous work has stressed the importance of heme a in the proton pump mechanism (15,18,31,33,(35)(36)(37). In the third phase, the substrate proton is transferred from the aqueous N-side, most likely to an OH Ϫ ligand of Cu B (38), which raises the E m of Cu B to a value much higher than that of all other centers.…”
Section: Assignment Of the Proton Transfer Reactionssupporting
confidence: 90%
“…7 and 33), even though these two events have the same proton-limited kinetics. This finding is consistent with the conclusion by Brändén et al (34) that protonation of the ''pump site'' controls this electron transfer, which is of considerable mechanistic interest because much previous work has stressed the importance of heme a in the proton pump mechanism (15,18,31,33,(35)(36)(37). In the third phase, the substrate proton is transferred from the aqueous N-side, most likely to an OH Ϫ ligand of Cu B (38), which raises the E m of Cu B to a value much higher than that of all other centers.…”
Section: Assignment Of the Proton Transfer Reactionssupporting
confidence: 90%
“…Direct observation of proton transfer through the key structures of these pathways by time-resolved infrared spectroscopy is expected to provide the means of conclusively identifying the pathway. The possibility that the low spin heme functions as the driving element of the proton pumping process has been proposed on several occasions back to 1978 (33)(34)(35)(36).…”
Section: Resultsmentioning
confidence: 99%
“…Papa et al (19) have suggested a regulatory function of this "direct" electron transfer reaction for the stoichiometry of proton pumping. They proposed that, even in the wild-type enzyme where, under normal conditions, Cu A -heme a electron transfer is at least 100-fold faster than Cu A -heme a 3 electron transfer, the latter may occur to a significant extent at high ⌬ H ϩ.…”
Section: Discussionmentioning
confidence: 99%